Legal protection against debtors from forced withdrawal of motorcycles by creditors under law no. 42 of 1999 - Samson Simatupang; Dina Andiza; Siti Nurhayati (Journal of Law Science, 2024)
A fiduciary guarantee certificate or deed is required for the execution or withdrawal of cars, according to Law Number 42 of 1999 respecting Fiduciary Guarantees. The question that this essay seeks to answer is: How are fiduciary guarantees governed in Indonesia? What factors lead to creditors forcibly retaking motorcycles? Regarding PT. Adira Dinamika Multifinance Branch 0601 Medan Graha Niaga's Law No. 42 of 1999 concerning Fiduciary Guarantees, how well-protected are debtors against attempts to forcibly withdraw motorized vehicles? This study employs a descriptive interviewing method in conjunction with an empirical research design. Primary, secondary, and tertiary legal sources are used as secondary data in qualitative research, and the research site is the PT office. Branch 0601 of Adira Dinamika Multifinance, Medan Graha Niaga The Fiduciary Guarantee Law, the Housing and Settlement Law, and the Copyright Law all regulate fiduciary guarantees in Indonesia. Aspects of Debtor Default, The creditor may withdraw the object of fiduciary collateral in order to transfer fiduciary objects and prevent them from being freely surrendered. The inference drawn is that fiduciary promises must underpin all commercial agreements in order to provide debtors with fair and transparent legal certainty. The government and police have been advised to keep offering debtors legal protection when it comes to carrying out fiduciary guarantees.